Edukasi Water Management kepada Masyarakat: Mencegah Kebakaran Lahan Gambut dan Pemanfaatan Lahan Gambut untuk Pertanian di Desa Kuta Padang Kabupaten Aceh Barat - Aulia, Muhammad Reza; Siregar, Mawaddah Putri Arisma; Fachruddin; Sufriadi; Agustiar; Safrika (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2023)
Education activities on water management and peatland utilization were carried out in Kuta Padang Villages, Bubon Subdistrict, West Aceh Regency. Involving 20 participants, including village officials, this water management education emphasized the importance of peat rewetting (Rewetting) and canal closure as the main strategies in addressing degradation and the risk of peatland fires. Through the Focused Group Discussion (FGD) method, participants were taught about fluctuations in groundwater levels, the identification of canal blocking construction, and the utilization of peatlands for agriculture. The results of the activity showed an increase in community understanding of the impact of peatland ecosystem damage and its connection to land fires. Education also discussed fluctuations in groundwater levels as a crucial element in water management, providing a better understanding of groundwater dynamics in peatlands. The selection of efficient food and horticultural crops for shallow peatlands became a focus in land utilization for agriculture.